PENGGUNAAN ANTIBIOTIK EMPIRIS PADA PASIEN PNEUMONIA - Pande Ayu Naya Kasih Permatananda; Ni Wayan Widhidewi (Universitas Respati Yogyakarta, 2021)
Empirical Use of Antibiotics in Pneumonia PatientsBackground: antibiotic as definitive therapy for pneumonia must be given within 8 hours, but on the other hand, to identify the cause of pneumonia will take several days so antibiotic are often given empirically. This will lead into the inaccuracy of choosing antibiotic for pneumonia patients. Inappropriate use of antibiotic can result in less effective treatment, decreased drug safety, increased resistance, and treatment costs. This analytical study of the use of antibiotics is important in relation to evaluating the use of antibiotic for pneumonia in medical practice. Objectives: : this study was to analyze and evaluate the patterns of antibiotic use in pneumonia patients, especially monotherapy and polytherapy antibiotics. Methods: the research location was in Wangaya Hospital, Denpasar City. Data collection was carried out retrospectively based on medical record data of pneumonia patients that hospitalized in 2017-2018. Patients diagnosed as pneumonia with code ICD-10 J.18, aged over 17 years, and receiving antibiotic therapy were included in the study. Results: we found the most widely used antibiotic were the combination of cefoperazone and levofloxacin (24.2%). Conclusion: there is one type of antibiotic combination that has a risk of major interactions that should be avoided.